Kairos Castle : Over de kunst van het juiste ogenblik - Hermsen, Joke J.; Vanackere, Luc; Vanhumbeeck, Sabine; De Jonge, Xavier (s.l. : Lannoo Publishing, 2017)
Cool, Alexandra ; Brasser, Alice ; Pielage, André ; Sala, Anri ; Zazzera, Antonella ; Gormley, Antony ; Smilde, Berndnaut ; Shiota, Chiharu ; Mercadier, Corinne ; Karavan, Dani ; Claerbout, David ; de Nie, Eric ; Keller, Evi ; Meertens, George ; Russell, Georgia ; Garcin, Gilbert ; Op de Beeck, Hans ; de Jonge, Jaap ; Johnson, Jay Mark ; Macchi, Jorge ; Baas, Maarten ; Simons, Marielin ; Hulzebos, Marlies ; Veldhoen, Martijn ; Buskens, Mynke ; de Staël, Nicolas ; Kisseleva, Olga ; Nkanga, Otobong ; Van Caeckenbergh, Patrick ; Bogers, Peter ; Rist, Pipilotti ; Quayola ; Horn, Rebecca ; Muller, Sofie ; Hertrich, Susanna ; Shingu, Susumu ; Pécastaing, Thierry
Kairos Castle, Kasteel van Gaasbeek, 1 april 2017 tot en met 18 juni 2017
boek